Improving the drilling process by its adaptive control - Vasilko, Karol (Manufacturing Technology Journal, 2020)
Experience with the use of NC machine tools shows that cutting conditions cannot be optimized without a more detailed knowledge of the machining process. The essence of the adaptive machining system lies in the response to he machining conditions (change in allowance, cutting width, material hardness). In doing so, it allowance a constant selected parameter, e. g. cutting force.
Keywords: machining; drilling; machinig time; cutting force.